2021
DOI: 10.1590/2177-6709.26.1.e2119248.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three different types of educational methods on implementation of proper oral hygiene behaviour prior to orthodontic treatment

Abstract: Objective: The aim of this study was to compare three teaching methods’ time and personnel requirements, and their effects on plaque and gingival indices. Methods: This study was a single-blind randomized controlled trial on fixed orthodontic appliance candidates (n = 90), assigned into a control group (n = 30) and two different study groups (n = 30 each). The control group received standard printed educational material and was assisted with verbal information. The study groups either received video-assisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, patients received oral hygiene management education at the beginning of orthodontic treatment, and it was confirmed that the degree of inflammation was the lowest among those with a high interest in oral health. Ozlu et al [ 42 ] reported that the Loë–Silness index is frequently used and that the second GI is often used as a secondary outcome to confirm the effectiveness of oral education in patients undergoing orthodontic treatment. However, the GI varies depending on the general condition of patients and the targeting area of the GI does not include the bonded dental surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients received oral hygiene management education at the beginning of orthodontic treatment, and it was confirmed that the degree of inflammation was the lowest among those with a high interest in oral health. Ozlu et al [ 42 ] reported that the Loë–Silness index is frequently used and that the second GI is often used as a secondary outcome to confirm the effectiveness of oral education in patients undergoing orthodontic treatment. However, the GI varies depending on the general condition of patients and the targeting area of the GI does not include the bonded dental surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no clinically available orthodontic guidelines that would standardize oral hygiene education among orthodontic patients [16,17]. The gap between the best available evidence regarding the general principles of oral hygiene in orthodontic patients to prevent dental caries and periodontal disease and its application in practice can be reduced through evidence implementation projects [18][19][20].…”
Section: Introductionmentioning
confidence: 99%